2020
DOI: 10.1111/jdv.16666
|View full text |Cite
|
Sign up to set email alerts
|

Erythema multiforme and Kawasaki disease associated with COVID‐19 infection in children

Abstract: Hence, corticosteroids could have prevented the initial development of AEGP. Lastly, to date SCARs have been reported with the use of ceftriaxone, but there is only one reported case of DRESS related to cefditoren, among other causes. 4,5 Surrounding the COVID-19 pandemic, many dermatoses are being reported as possibly SARS-CoC-2 induced. Here, we highlight the importance of considering other etiologies as causes of skin lesions arising on the background of SARS-CoV-2 infection. Special effort has to be made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
114
0
29

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(144 citation statements)
references
References 9 publications
1
114
0
29
Order By: Relevance
“…The varied cutaneous presentations, histopathological ndings, and other details are tabulated in table 3. Reference [16], [19], [20], [21], [24], [25], [26], [27] [17], [18], [ The majority of the children showed erythematous maculopapular eruptions, which is generally the commonest cutaneous presentation in any viral illness, however, a closer look in our study subjects throws up several contradicting observations. For instance, instead of general cephalocaudal distribution in any viral exanthem, here the cases showed involvement of acral region of feet and hands.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The varied cutaneous presentations, histopathological ndings, and other details are tabulated in table 3. Reference [16], [19], [20], [21], [24], [25], [26], [27] [17], [18], [ The majority of the children showed erythematous maculopapular eruptions, which is generally the commonest cutaneous presentation in any viral illness, however, a closer look in our study subjects throws up several contradicting observations. For instance, instead of general cephalocaudal distribution in any viral exanthem, here the cases showed involvement of acral region of feet and hands.…”
Section: Resultsmentioning
confidence: 89%
“…[22] Generalized exanthematous lesion with palmer edema, cervical lymphadenopathy, glossitis and desquamation of extremities; Kawasaki disease like presentation, was reported in a 3 years male child with negative RT PCR but ground glass consolidation in CT chest suggestive of COVID pneumonia. [18] Additionally, Bursal et al reported non-acral erythematous maculopapular rash starting on the face and extending to trunk and extremities in 3 of their COVID positive patients. [28] The site of lesion was feet alone in 120 cases, mostly at the dorsal surface of toes & sometimes on the lateral margin of feet.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, in Peru the cases in children under 11 increased from 1.9% of total cases on 12 May10 to 2.6% on 26 May11 and from 1.1% to 1.6% in 12-17 year olds. This happened as Kawasaki-like cases with prolonged fever, rash, and hyperinflammatory shock in young children started to be reported in Europe12131415 and the United States 1617. On 14 May, this syndrome was called multisystem inflammatory syndrome in children (MIS-C) 18.…”
mentioning
confidence: 99%